KNOWLEDGE ON NURSING STUDENT OF UNIVERSITAS MUHAMMADIYAH GOMBONG ABOUT BREAST SELF EXAMINATION - Reni Purwo Aniarti (Universitas Pahlawan Tuanku Tambusai, 2021)
ABSTRACT Introduction: Breast cancer have the highest incidence rate in Indonesia, namely 65.858 people (16.6%) of all types of cancer. Early detection of breast cancer can be done with Breast Self Examination (BSE). Exercise BSE regulary can preent the early development of breast ancer. Aims of study was to determine BSE knowledge with behaviour on nursing student Universitas Muhammadiyah Gombong. Method:The method of this research is descriptive with a cross sectional design conducted on nursing student Universitas Muhammadiyah Gombong with total sample of 80 participat. Data collection using a questionnaire, univariate data analyzed using SPSS softwere. Result: The result of analysis show that 61,26 % of respondent have sufficient knowledge, 27,5 % have good knowledge and 11,25 % have low knowledge of BSE. As many as 28,75 % of respondent have good behaviour, 48,75 % have moderat behaviour and 22,50 % have low behaviour in implementation BSE. Conclusion: Nursing student of Universitas Muhammadiyah Gombong have sufficient knowledge and moderat behaviour in BSE. Keywords: knowledge, behaviour, breast self examination